Елементи синтезу вентильного двигуна з постійними магнітами - Ткачук, Василь Іванович; Біляковський, Ігор Євгенович (НТУ "ХПІ", 2010)
The elements of synthesis of Brushless d.c. Motor with permanent magnets on a rotor and pseudo by U-similar stator is offered. The mathematical model of project calculation of main geometrical dimensions of such Motor is based on these elements.
The elements of synthesis of brushless d.c. motor with permanent magnets
Keywords: електропривід регульований; потужність; перетворювач електромеханічний; комутатор електронний; система керування; статор